2001
DOI: 10.1159/000047845
|View full text |Cite
|
Sign up to set email alerts
|

Hair Growth Pattern in Nude Mice

Abstract: Nude mice are not bald but instead show an ‘abortive’ reduced hair growth on different sites of the integument. An albino (NMRI-nu) and a pigmented (C57BL/6-nu) strain of nude mice were examined as to whether the regional distribution pattern of this anagen hair proliferation is subject to the same ontogenetic development as in hairy mice. Hairy mice of both strains served as a comparison. Hair distribution was documented macroscopically by drawing and photography in a total of 415 mice of both sexes up to 421… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
2
28
1
Order By: Relevance
“…The macroscopic appearance of hair growth of the control nude mice was documented as a few short, crippled, bent hair shafts emerging from the HFs. Very few follicles, of locally variable density, occur in the dorsal skin (Köpf-Maier et al, 1990;Militzer, 2001;Rigdon & Packchanian, 1974); and only during a short anagen growth phase (Iversen & Iversen, 1967). Here, we were able to observe an incomparable hair growth pattern in CZ-treated mice with other treated groups (Figure 1).…”
Section: Discussionsupporting
confidence: 51%
“…The macroscopic appearance of hair growth of the control nude mice was documented as a few short, crippled, bent hair shafts emerging from the HFs. Very few follicles, of locally variable density, occur in the dorsal skin (Köpf-Maier et al, 1990;Militzer, 2001;Rigdon & Packchanian, 1974); and only during a short anagen growth phase (Iversen & Iversen, 1967). Here, we were able to observe an incomparable hair growth pattern in CZ-treated mice with other treated groups (Figure 1).…”
Section: Discussionsupporting
confidence: 51%
“…Militzer (25) used nude mouse of the pigmented strain (C57BL͞ 6-Foxn1 nu ) to visualize regions in the anagen phase of the hair growth and recorded the pattern change for up to 400 days. He found that young Foxn1 nu mice have a few broad traveling bands of anagen phase on the skin, but later (Ͼ200 days), those patterns are replaced by one or a few periodically appearing, (26) reported a mutant line, named cryptothrix (crh), that had similar waves.…”
Section: Resultsmentioning
confidence: 99%
“…There are no obvious structural differences between normal and athymic mice in the appearance of the outer root sheath, dermal papilla, bulb and sebaceous glands. In the athymic mice the hairs are bent and coiled in the upper dermis and they usually fail to penetrate the epidermis [32]. So, athymic mice used for the studies about hair growth effect of new therapy [33,34].…”
Section: Discussionmentioning
confidence: 99%